Latinos in the United States and in Spain: the impact of ethnic group stereotypes on labour market outcomes - Ruta Yemane; Mari\~na Fernández-Reino (Journal of Ethnic and Migration Studies, 2021)
This is the first harmonised correspondence study on the recruitment behaviour of employers in the US and in Spain. By comparing the call-back rates of Latino minority and majority group applicants, we measure the labour market discrimination that Latinos experience in these two national contexts. Due to their proximity in terms of culture and language, Latinos are expected to experience less discrimination in Spain than in the US. This is supported by our findings, as the level of discrimination against Latinos in the US is high and statistically significant, while we find no evidence of statistically significant discrimination against Latinos in Spain. In line with research on the intersection between ethnicity and gender in stereotyping, we find gender differences regarding discrimination in both countries, though in opposite directions. While Latino males are more discriminated than Latino females in the US, Latino females experience more discrimination than their male counterparts in Spain, who are not treated differently from Spanish native men. Our results indicate that ethnic group stereotypes are country-specific and different for males and females of the same ethnicity. Moreover, we find partial evidence that ethnic group stereotypes can be counteracted when favourable information on warmth and competence is provided.
Keywords: 330; harmonised field experiment; Latinos; ethnic group stereotypes; labour market discrimination